Clinical case report: Malan and Marshall-Smith Syndrome (Research, Society and Development, 2025)
The nuclear factor I/X (NFIX) gene encodes a ubiquitously expressed transcription factor whose mutations lead to two allelic disorders characterized by developmental, skeletal, and neural abnormalities, namely Malan syndrome (SMAL) and Marshall–Smith syndrome (SMS). SMAL-associated NFIX mutations cluster mainly in exon 2 and are eliminated by nonsense-mediated decay (NMD) leading to NFIX haploinsufficiency, whereas SMS-associated NFIX mutations cluster in exons 6–10 and escape NMD and result in the production of dominant-negative mutant NFIX proteins. This work aimed to report a clinical case of a male patient diagnosed with SMS at 2 months of age, and later with SMA; presenting severe respiratory complications since birth. SMAL has been shown to be an overgrowth disorder characterized by a slender habitus, long hands, and advanced bone age, moderate to severe intellectual disability, an unusual facial phenotype consisting of a long, triangular face with a prominent forehead, everted lower lip, and prominent chin, and behavioral problems. Accelerated bone maturation and moderate to severe global developmental delay/intellectual disability are the main clinical manifestations of patients with SMAL, who present with a constellation of unique symptoms, including orofacial dysmorphisms, accelerated bone maturation and dysplasias, mental retardation, and respiratory disease. It was concluded that clinical recognition of physical, developmental, and behavioral features is important not only for diagnosis, prognosis, and family counseling, but also increases our understanding of the biological basis of the human physical and behavioral phenotype.